RESILIENSI SOSIAL KOMUNITAS NELAYAN PESISIR DALAM MENGHADAPI FENOMENA PERUBAHAN IKLIM - Kaseng, Ernawati Syahruddin; Suhaeb, Firdaus W; Idang, Sri Wahyuni Handayani; Dahlan, Mubarak (Social Landscape Journal, 2024)
This study was conducted with the aim of determining the resilience of fishing communities in Barru District, Barru Regency in facing the phenomenon of climate change. This research is a qualitative descriptive research. Data collection techniques use observation, interviews and documentation. Data analysis techniques use descriptive-qualitative analysis through the stages of data reduction, data presentation and conclusions. The results of this study show that traditional fishing communities and modern fishermen in the coastal areas of Barru District have felt the impact of climate change that affects the lives of fishing communities in environmental, socio-economic and physical aspects. For this reason, the ability of fishing communities to reduce vulnerability is demonstrated through adaptability at the level of stability, recovery and transformation. Resilience at the level of stability is carried out by surviving by utilizing family savings. At the level of recovery, the adaptation capacity of traditional fishing communities and modern fishing communities can be said to be high through survival by utilizing Human Resources (HR) assets by looking for other jobs outside of fishing activities but having low adaptation when dependent on bad weather. Traditional coastal fishing communities have limited supporting facilities in the process of marine activities so that they cannot be said to be at the level of transformation. Modern fishing communities have been at a level of transformation by increasing vessel tonnage, procuring new vessels and replacing fishing gear.